DEVELOPMENT OF ELECTRO -TRAWL SYSTEM IN MARINE ENVIRONMENT. - NAMBOODIRI, K SREEDHARAN; VIJAYAN, V (Fishery Technology, 2017)
High voltage pulsed current produced on board a trawleris fed to electrodes distributed along the foot rope of a trawlnet through 2 core TRS cable which builds up a homogeneouselectrical field around the net mouth. By comparative fishingtests with the electrified and non-electrified 32 m. long wingtrawl net, the increase in total catch of shrimps and fisheswas found to be 19.8 and 36%, respectively.